Tutoring to Overcome Learning Difficulties in Middle School Students - Mustopa, Aditya Triana (Jurnal Eksplorasi Bimbingan dan Konseling, 2024)
This study aims to analyze students' learning difficulties through Tutoring Services that focus on students' interests and motivations in learning in order to overcome Student Learning Difficulties. The research method used is Literature Study. Based on the results of the Literature Study, it is obtained that Tutoring Services can overcome students' learning difficulties. Tutoring Services can solve learning problems and also help students in (a) having positive attitudes and learning habits, (b) Having high motives for lifelong learning, (c) Having effective learning skills or techniques, (d) Having skills in setting goals and educational planning, (e) Having mental readiness and ability to face exams.